1992
DOI: 10.2527/1992.70123994x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of nutrition and season on the onset of puberty in the beef heifer

Abstract: Age at puberty is a major determinant of lifetime reproductive efficiency of beef cows. Research conducted during the past 20 yr has documented the major endocrine events leading to first ovulation in heifers. The critical event seems to be a prepubertal increase in pulsatile LH secretion. Environment influences timing of puberty onset in beef heifers. Nutrition and season are two of the better-defined variables that have been studied. Age at puberty is related inversely to plane of nutrition. The effect of nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
128
4
21

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 190 publications
(160 citation statements)
references
References 88 publications
7
128
4
21
Order By: Relevance
“…However, in the present study, we could not find any significant effect of improved feeding on puberty age in the Malpura ram lambs, possibly owing to achievement of critical weight by ram lambs required for attainment of puberty in both the groups, as the growth rate has little effect on the rate of sexual maturation after a certain critical weight has been achieved (Schillo et al, 1992).…”
Section: Discussioncontrasting
confidence: 85%
“…However, in the present study, we could not find any significant effect of improved feeding on puberty age in the Malpura ram lambs, possibly owing to achievement of critical weight by ram lambs required for attainment of puberty in both the groups, as the growth rate has little effect on the rate of sexual maturation after a certain critical weight has been achieved (Schillo et al, 1992).…”
Section: Discussioncontrasting
confidence: 85%
“…The establishment of LH pulsatility is responsible for the initiation of cyclicity in, for example, pubertal heifers [82]. The inhibition of LH pulsatility before puberty, and consequently the inhibition of ovarian cyclicity, is in these animals probably due to a negative feedback by estradiol secreted by the ovary.…”
Section: Regulation Of Gonadotrophinsmentioning
confidence: 99%
“…The inhibition of LH pulsatility before puberty, and consequently the inhibition of ovarian cyclicity, is in these animals probably due to a negative feedback by estradiol secreted by the ovary. Among the factors that are associated with onset of puberty, attainment of a critical level of body fat is important [82]. This strongly suggests that there are links between the reproductive endocrine system and metabolic status of the animal, which could also apply to non-adaptive cows in early lactation.…”
Section: Regulation Of Gonadotrophinsmentioning
confidence: 99%
“…Age at puberty in cattle is highly influenced by nutritional status and body development (Schillo et al, 1992). Hence, nutritional interventions that improve nutrient utilization, body fat accretion, and increase circulating concentrations of hormones that facilitate the puberty process, such as IGF-I and leptin, are known to hasten puberty attainment in heifers (Williams et al, 2002; Cooke et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…(1) puberty in cattle is highly influenced by nutritional status and body development (Schillo et al, 1992), including growth rate, body fat accretion, and circulating concentrations of hormones associated with nutrient metabolism and lipogenesis such as IGF-I and leptin (Williams et al, 2002;Cooke et al, 2008), and (2) management systems that stimulate metabolic imprinting enhance nutrient metabolism and body fat accretion in cattle (Graugnard et al, 2010;Scheffler et al, 2014;Moriel et al, 2014a). Supporting our rationale, Moriel et al (2014b) reported reduced age and BW at puberty in heifers weaned at 72 days of age and fed a high-concentrate diet for 90 days compared with forage-fed cohorts weaned at 252 days of age.…”
mentioning
confidence: 99%